Diabetic macrophage small extracellular vesicles-associated miR-503/IGF1R axis regulates endothelial cell function and affects wound healing - Wang, Jianqiang; Han, Yuanshan; Huang, Fang; Tang, Liuhuan; Mu, Jianfei; Liang, Ying (Frontiers in Immunology, 2023)
Diabetic foot ulcer (DFU) is a break in the skin of the foot caused by diabetes. It is one of the most serious and debilitating complications of diabetes. The previous study suggested that dominant M1 polarization during DFU could be the leading reason behind impaired wound healing. This study concluded that macrophage M1 polarization predominates in DFU skin tissue. iNOS was increased in HG-induced M1-polarized macrophages; conversely, Arg-1 was decreased. Macrophage pellets after HG stimulation can impair endothelial cell (EC) function by inhibiting cell viability, tube formation and cell migration, indicating M1 macrophage-derived small extracellular vesicles (sEVs) -mediated HUVEC dysfunction. sEVs miR-503 was significantly upregulated in response to HG stimulation, but inhibition of miR-503 in HG-stimulated macrophages attenuated M1 macrophage-induced HUVEC dysfunction. ACO1 interacted with miR-503 and mediated the miR-503 package into sEVs. Under HG stimulation, sEVs miR-503 taken in by HUVECs targeted IGF1R in HUVECs and inhibited IGF1R expression. In HUVECs, miR-503 inhibition improved HG-caused HUVEC dysfunction, whereas IGF1R knockdown aggravated HUVEC dysfunction; IGF1R knockdown partially attenuated miR-503 inhibition effects on HUVECs. In the skin wound model in control or STZ-induced diabetic mice, miR-503-inhibited sEVs improved, whereas IGF1R knockdown further hindered wound healing. Therefore, it can be inferred from the results that the M1 macrophage-derived sEVs miR-503 targets IGF1R in HUVECs, inhibits IGF1R expression, leads to HUVEC dysfunction, and impedes wound healing in diabetic patients, while packaging miR-503 as an M1 macrophage-derived sEVs may be mediated by ACO1.